Synthesis of some benzimidazole derivatives endowed with 1,2,3-triazole as potential inhibitors of hepatitis C virus - Youssif Bahaa G. M.; Mohamed Yaseen A. M.; Salim Mohammed T. A.; Inagaki Fuyuhiko; Mukai Chisato; Abdu-Allah Hajjaj H. M. (Acta Pharmaceutica)
New derivatives of 2-thiobenzimidazole incorporating triazole moiety were synthesized, characterized and tested in vitro for antiviral activity against hepatitis C virus (HCV) and hepatitis B virus (HBV). Their cytotoxicity was determined by the reduction in the number of viable cell. All of the synthesized compounds are inactive against HBV and some showed activity against HCV. In particular, two compounds showed significant activity, 2-{4-[(1-benzoylbenzimidazol-2-ylthio)methyl]-1H-1,2,3-triazol-1-yl}-N-(p-nitro-phenyl)-acetamide (13) and 2-(4-{[1-(p-chlorobenzoyl)-benzimidazol-2-ylthio)methyl]-1H-1,2,3-triazol-1-yl}-N-(p-nitrophenyl)-acetamide (17). The results give an insight into the importance of the substituent at position 2 of benzimidazole for the inhibition of HCV.